(3ebGdI aj EjVGM ZdW CHj Ydi Hf GdgjKe aj GdTcd GdChd ef GdebGdI GdYGTQI ef cJGH EbdjOS aj GdCUhds - (3fLe GdOjf CHh GdaJhM CMeO Hf eMeO Hf GdSQj hcGf jYQa HGHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bGd Cfi fXQJ ebGdI dGHi Ydi Hf GdgjKe bO YfhfgG HbSeI GdebOGQjf GdeNJdajf GdePchQjf ai GdebGdI GdYGTQI ef cJGH GbdjOS ai GdGUhd s
(3BNQgG (B:s
(3hEf CfG YOOJ LejY GdcJH GdNGQLI Yf cJGH EbdjOS GdJi GSJYed ajgG gPG GdTcd hEfgG dGJUM EdG Hg cGf Pdc cGdaVd GdPi dGjJMJGL Edjg Je Gdbhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs